Percutaneous nephrolithotomy in children: A preliminary report - Ahmad A. Elderwy; Mohamed Gadelmoula; Mohamed A. Elgammal; Ehab Osama; Hamdan Al-Hazmi; H. Hammouda; Esam Osman; Medhat A. Abdullah; Khalid Fouda Neel (Urology Annals, 2014)
Objectives: The recurrence of pediatric nephrolithiasis, the morbidity of repeated open surgical treatment as well as our experience in percutaneous nephrolithotomy (PNL) in adult patients, all derived us to shift to PNL for managing renal stones >1.5 cm in pediatric patients. Our aim of this study is to evaluate the safety and efficacy of PNL in pediatric patients. Materials and Methods: During the period of the month between May 2011 and April 2013, 38 children (47 renal units) underwent PNL for renal stones 1.5-5 cm in length. Patient demographics, stone characteristics, and clinical outcome were prospectively studied. Data of those who underwent conventional and tubeless PNL were compared. Median follow-up period was 12 months (range: 6-24). Results: The median age at presentation was 8-year (range: 3-12). The operative time ranged from 30 to 120 min (median 90). Overall stone clearance rate was 91.5% after single PNL. The median hospital stay was 3 days. Auxiliary procedures were successful for the remaining 4 patients (nephroscopic clearance in one and shockwave lithotripsy in 3). Tubeless PNL was performed in 17 renal units with a comparable outcome to conventional ones. The perioperative complications were noted in 5/47 (10.6%) of all procedures (Clavien Grade II in 4 and Clavien Grade IIIa in 1) and were managed conservatively. Conclusions: Percutaneous nephrolithotomy for renal stones in pediatric patients is safe and feasible if performed by a well-experienced endourologist. Tubeless PNL is a better choice for children.